2016
DOI: 10.1111/jon.12326
|View full text |Cite
|
Sign up to set email alerts
|

Optical Coherence Tomography for the Detection of Remote Optic Neuritis in Multiple Sclerosis

Abstract: Optic neuritis is associated with thinning in multiple regions of the retina. Optic neuritis eyes can be differentiated most accurately from nonoptic neuritis eyes using OCT. Our work suggests a potential role for OCT in documenting a remote history of optic neuritis to corroborate a diagnosis of MS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…These findings suggest that the papillomacular bundle is preserved in SCA10 and that RNFL thinning is not caused by a loss of cells in the GCL, corroborating the conclusions reported by Alvarez et al 21 . They also suggest that retinal degeneration in SCA3 is similar to the degeneration that occurs in multiple sclerosis 23 but different from the degeneration in idiopathic Parkinson's disease, in which although the RNFL becomes thinner as the patient's clinical condition worsens, it is accompanied by neuron loss in the GCL 24,25 , and also different from the degeneration in Alzheimer's disease, where there is mainly loss of neurons in the GCL 26,27. It is also different from the pattern found in SCA1, where there is more neuronal loss in the temporal region, suggesting that the papillomacular bundle is affected 28 .…”
Section: Discussionmentioning
confidence: 95%
“…These findings suggest that the papillomacular bundle is preserved in SCA10 and that RNFL thinning is not caused by a loss of cells in the GCL, corroborating the conclusions reported by Alvarez et al 21 . They also suggest that retinal degeneration in SCA3 is similar to the degeneration that occurs in multiple sclerosis 23 but different from the degeneration in idiopathic Parkinson's disease, in which although the RNFL becomes thinner as the patient's clinical condition worsens, it is accompanied by neuron loss in the GCL 24,25 , and also different from the degeneration in Alzheimer's disease, where there is mainly loss of neurons in the GCL 26,27. It is also different from the pattern found in SCA1, where there is more neuronal loss in the temporal region, suggesting that the papillomacular bundle is affected 28 .…”
Section: Discussionmentioning
confidence: 95%
“…PMB thickness remains of uncertain clinical significance. One study of MS patients reported PMB thickness as the best model to discriminate between remote ON and non-ON eyes, 13 whereas another demonstrated that adding PMB measurements to OCT does not increase sensitivity to detect remote ON. 14 Interestingly, our median PMB thickness (27 µm) was lower than previously published data in MS-ON (mean = 35–40 µm).…”
Section: Discussionmentioning
confidence: 99%
“…As seen in Table 1, 8 cases were included in the analysis (3 female, 5 male). Median age at disease onset was 13 (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) years. All patients had a MOG titer of 1:100-1:1,000 and had ON as determined by inclusion criteria.…”
Section: Patient Characteristicsmentioning
confidence: 99%
“…172 RNFL thickness is reduced in ON and MS patients compared with healthy controls (Figure 2). This is seen using OCT in eyes with prior ON, 171,[173][174][175][176][177][178][179][180][181][182][183][184][185][186][187] particularly temporally and inferiorly. 176,177,188 The majority of studies also identified reduced pRNFL thickness in MS patients without prior history of ON (MS-NON), although to a lesser extent.…”
Section: Oct In Multiple Sclerosismentioning
confidence: 92%